2020
DOI: 10.1002/jbio.202000340
|View full text |Cite
|
Sign up to set email alerts
|

Effective photodynamic treatment of Trichophyton species with Rose Bengal

Abstract: Photodynamic therapy (PDT) with Rose Bengal has previously achieved eradication of Trichophyton rubrum infections causing toenail onychomycosis; however, its antifungal activity against other clinically relevant dermatophytes has yet to be studied. Here, we test the efficacy of PDT using Rose Bengal (140 μM) and 532 nm irradiation (101 J/cm 2) against Trichophyton mentagrophytes and Trichophyton interdigitale spores, in comparison to T. rubrum. A significant reduction (>99%) of T. mentagrophytes and T. interdi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…These photodynamic therapies are based on the specific absorption of the laser energy by fungal chromophores which are not present in the human tissues, therefore causing a photothermic and photochemical effect, destroying the fungal hyphae, depending in main parameters such as wavelength, pulse duration, frequency, irradiation area, and the number and timing of the treatments. This absorption thus causes photothermal and photochemical effects that destroy the hyphae of the fungus, without causing systemic effects [ 28 , 29 ]. Specifically, the violet 405 nm wavelength has been described as causing oxidative stress in fungal cells, targeting nicotinamide adenine dinucleotide phosphate-oxidase (NADPH-oxidase) and cytochrome C oxidase, increasing its production of the highly volatile reactive oxygen species (ROS), which have antimicrobial effects.…”
Section: Introductionmentioning
confidence: 99%
“…These photodynamic therapies are based on the specific absorption of the laser energy by fungal chromophores which are not present in the human tissues, therefore causing a photothermic and photochemical effect, destroying the fungal hyphae, depending in main parameters such as wavelength, pulse duration, frequency, irradiation area, and the number and timing of the treatments. This absorption thus causes photothermal and photochemical effects that destroy the hyphae of the fungus, without causing systemic effects [ 28 , 29 ]. Specifically, the violet 405 nm wavelength has been described as causing oxidative stress in fungal cells, targeting nicotinamide adenine dinucleotide phosphate-oxidase (NADPH-oxidase) and cytochrome C oxidase, increasing its production of the highly volatile reactive oxygen species (ROS), which have antimicrobial effects.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated the effectiveness of PDT in onychomycosis patients using different photosensitizers, such as aminolevulinate (ALA) [10], MAL [6], MB [11] and rose Bengal [12], curcumin [13], and compared its efficacy in monotherapy with available drugs [14]. PDT appears to be more effective than amorolfine for the treatment of non-dermatophyte onychomycosis [15].…”
Section: Discussionmentioning
confidence: 99%
“…This result confirms the potency of rose bengal as a photodynamic agent. In a previous study, 44,45 photoactivation of rose bengal by a green laser emitting at 532 nm generated a significant amount of ROS that eradicated pathogenic fungi at the same power (90 mW in continuous wave mode). Other studies have demonstrated the high quantum yield of singlet oxygen production by rose bengal, 46 which accounts for ~75% of the ROS generated.…”
Section: Photodynamic Therapy Of Breast Cancer Cells Using Rose Benga...mentioning
confidence: 92%